2013
DOI: 10.1177/0300985813480510
|View full text |Cite
|
Sign up to set email alerts
|

Use of Computed Tomography and Histopathologic Review for Lung Lesions Produced by the Interaction BetweenMycoplasma hyopneumoniaeand Fumonisin Mycotoxins in Pigs

Abstract: Mycoplasma hyopneumoniae has a primary role in the porcine respiratory disease complex (PRDC). The objective of this study was to determine whether fumonisin mycotoxins influence the character and/or the severity of pathological processes induced in the lungs of pigs by Mycoplasma hyopneumoniae. Four groups of pigs (n ¼ 7/group) were used, one fed 20 ppm fumonisin B 1 (FB 1 ) from 16 days of age (group F), one only infected with M. hyopneumoniae on study day 30 (group M), and a group fed FB 1 and infected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Finally, Pósa et al. () showed that pigs receiving feed contaminated with Fumonisin B elicited more severe lung lesions upon M. hyopneumoniae challenge infection compared to pigs fed with non‐contaminated feed. Pigs that received feed contaminated with the mycotoxin deoxynivalenol (DON) did not develop more severe disease and lesions upon experimental M. hyopneumoniae infection than pigs fed with non‐contaminated feed (Michiels et al., ).…”
Section: Pathogenicitymentioning
confidence: 99%
“…Finally, Pósa et al. () showed that pigs receiving feed contaminated with Fumonisin B elicited more severe lung lesions upon M. hyopneumoniae challenge infection compared to pigs fed with non‐contaminated feed. Pigs that received feed contaminated with the mycotoxin deoxynivalenol (DON) did not develop more severe disease and lesions upon experimental M. hyopneumoniae infection than pigs fed with non‐contaminated feed (Michiels et al., ).…”
Section: Pathogenicitymentioning
confidence: 99%
“…The most mycotoxins have strong immunosuppressive effects and often compromise animals and human health provoking development of secondary bacterial infections (Stoev et al, 2000) or deteriorating some existing diseases (Pósa et al, 2011(Pósa et al, , 2013. It is well known, that Fumonisin B 1 (FB 1 ) is one of the most frequent contaminant of the feeds for pigs in all over the world (Dutton, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a heavy progression of Pasteurella multocida (Halloy et al, 2005) or porcine reproductive and respiratory syndrome (PRRS) virus infections in swine (Ramos et al, 2010) were seen when the same animals were compromised by feed exposure to FB 1 . There are also some recent reports about aggravations of pathological infections in pigs, when fed on FB1 contaminated diet (Pósa et al, 2011(Pósa et al, , 2013. Nevertheless, the data available about the possible interaction between FB 1 and some frequent infectious pathogens in pigs can be evaluated as insuficient and scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The unceasing development of CT equipments have resulted in continuously improving image resolution that, together with increasing scanning speed, makes possible the examination of smaller and smaller details. Its ability to follow the course of the disease in the same animal without the need to sacrifice is of great importance as well as its potential application for studying other diseases in a longitudinal manner just as proved recently by early detection of pneumonia and monitoring the pathological events during its progression [20,21]. …”
Section: Discussionmentioning
confidence: 99%